Juridical Review of Violence Committed by Police Officers Against Criminal Suspects - Rahmat Bakri (Indonesian Research Journal in Legal Studies, 2025)
This research aims to analyze in depth the legal aspects related to acts of violence by police officers against suspects, as well as evaluate the effectiveness of laws and regulations in providing legal protection to suspects. The method used is normative legal research, with a legislative and conceptual approach. Data was collected through literature studies using primary, secondary, and tertiary legal materials. The results of the study show that: 1) Acts of violence by police officers, such as beatings, torture, and shootings, still occur and are contrary to human rights principles and provisions in the Criminal Code, the Police Law, and various Police Chief Regulations. 2) Violence by police officers still often occurs, including beatings, torture, and actions that cause the death of the suspect. Within 2024, in Central Sulawesi, three cases of violence by police officers were found that led to ethical sanctions in the form of disrespectful dismissals (PTDH). Although there is a legal framework that prohibits violence and guarantees the rights of suspects, implementation on the ground is still weak. Therefore, it is necessary to strengthen internal supervision, policy reform, and improve human rights education for police officers so that the rights of suspects can be protected in real terms.